Spatial Efficiency Enhancement of Thailand–Myanmar’s Cross–border Passes in Chiang Mai Province - Sukdanont, Sumalee; Pechdin, Watchara; Tawinnorppanan, Parcharapat (NIDA Development Journal, 2018)
This study aims to propose appropriate guideline for enhancement of potentiality of the communities located near Thai-Myanmarese checkpoints for border trade which are Kiw Pha Wok Temporary Border Checkpoint and Lak Taeng Temporary Border Checkpoint in Chiang Mai Province. The study take into account the in-depth interview, field survey, and related information and border trade statistics. The result shows that, due to different characteristic of each border checkpoint, they need different appropriate guidelines for development. Relevant rules, regulations, and development guidelines need to be reformed and suitably applied to each area, depending on the area’s characteristic. Government authorities, together with local authorities should join in this reform process. Moreover, there should be an establishment of the unit that is responsible for border economic issues and cooperate closely with Thai and Myanmar local authorities. These recommendations are expected to help develop efficiency of Thai-Myanmar border trade and enhance potentiality of the border communities in Chiang Mai Province.